Negative ions of atoms, diatomic and triatomic molecules - Gretchikhin, Leonid I.; Kamarouskaya, Viktoryia M. (Vojnotehnički glasnik / Military Technical Courier, 2015)
Electron affinity is not determined by solving the Schrödinger equation but by using sets of different types of interactions. In atoms, the coupling between the external electron and the integrated electric dipole moment of a neutral atom mainly contributes to electron affinity. In diatomic molecules, electron affinity is defined mainly by the interaction of the external electron and the integrated electric dipole moment of the closest ion. In triatomic molecules, the external electron interacts with all integrated dipole moments of the positive core.
Keywords: dipole moment; negative ion; atom; diatomic molecule; triatomic molecule